Analysis of Raw Natural Montmorillonite (MMT) from Marapi Volcanic Ash and Its Potential as an Adsorbent - Nawiyah, Nawiyah; Jonuarti, Riri; Darvina, Yenni; Hidayat, Rahmat; Syafri, Syafri (Journal of Experimental and Applied Physics, 2025)
Volcanic ash consists of fine particles that are ejected into the atmosphere during an eruption of a volcano. The volcanic ash that will be tested in this study comes from the Aia Angek area of West Sumatra, which erupted in December 2023 to February 2024. The goal of this research was to assess the quantity of montmorillonite found in the volcanic ash originating from Marapi. In order to reach this objective, various examinations were conducted for characterization utilizing XRF, XRD, FTIR and SEM. The XRF data results show that the largest montmorillonite elements in volcanic ash are SiO2 dan Al2O3. The XRD test results show that there are 6 types of montmorillonite contained in Marapi volcanic ash, namely Chlorite-vermiculite-montmorillonite, Montmorillonite (Clay), Illite-Montmorillonite regular, Monmorillonite, Montmorillonite 15-A and Montmorillonite heated. The FTIR test results show that the peak band 3669-467/cm contains the chemical composition of montmorillonite. Based on the SEM test analysis, it shows the morphology of montmorillonite from Marapi volcanic ash with a particle size of 301,9 nm and a porosity size of 151,6 nm. Thus, based on the results of the five characterizations carried out, it is known that the Marapi volcanic ash does contain complex montmorillonite.